1987
DOI: 10.1002/jbt.2570020106
|View full text |Cite
|
Sign up to set email alerts
|

Chlordecone does not interfere with hepatic repair after carbon tetrachloride or partial hepatectomy

Abstract: The effect of chlordecone (CD) on hepatic repair, measured either as recovery of microsomal enzymatic functions or as the induction of cytosolic thymidine kinase (TK) activity, was evaluated in rats given carbon tetrachloride (CCl4). Carbon tetrachloride was administered to CD-potentiated and control animals using doses of this hepatotoxin which produce similar degrees of damage at 24 hours in both groups of animals (6 and 100 microliters CCl4 per 100 g body weight, respectively). Chlordecone had no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1987
1987
1991
1991

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…These studies strengthened the view that the onset of hepatocellular repair processes is a significant aspect of the recovery of rat liver after limited injury, and they provided the basis for the hypothesis that the suppression of the repair processes may be playing a role in the amplification of CC4 liver cell injury by chlordecone (1,7,8). While other work has not supported this hypothesis (9) The polyamines, ubiquitous compounds (10) present in eukaryotic cells, are considered important for cell growth and proliferation leading to tissue regeneration (11)(12)(13). Important enzymatic steps involved in the synthesis and turnover of polyamines are shown in Fig.…”
Section: Introductionmentioning
confidence: 98%
“…These studies strengthened the view that the onset of hepatocellular repair processes is a significant aspect of the recovery of rat liver after limited injury, and they provided the basis for the hypothesis that the suppression of the repair processes may be playing a role in the amplification of CC4 liver cell injury by chlordecone (1,7,8). While other work has not supported this hypothesis (9) The polyamines, ubiquitous compounds (10) present in eukaryotic cells, are considered important for cell growth and proliferation leading to tissue regeneration (11)(12)(13). Important enzymatic steps involved in the synthesis and turnover of polyamines are shown in Fig.…”
Section: Introductionmentioning
confidence: 98%
“…A comparison of the dose-response curves allows the selection of doses of CC4 which are equieffective in producing hepatic damage in chlordecone-treated and control animals. Two such equieffective doses of CC4 (6 and 100 p1/100 g BW in the chlordecone and control groups, respectively) have been used in experiments examining the effects of chlordecone on hepatic repair processes (9). The present report has also demonstrated that chlordecone administration induces cytochrome P-450 and causes an increase in the covalent binding of CC14-derived metabolites to microsomal protein and lipid in vivo; this action may play a role in chlordecone-induced potentiation of CC14 hepatotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The present study has reexamined the effect of chlordecone on the metabolism of CC14 to reactive products in vivo by measuring the covalent binding of [14-C]-CC14 metabolites to microsomal protein and lipid. A study of possible effects of chlordecone on hepatic repair processes is reported elsewhere in this issue (9).…”
Section: Introductionmentioning
confidence: 98%